2020
DOI: 10.3390/ejihpe10020041
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Impact Measures of Grit among Nursing Students: A Journey Emblematic of the Koi Fish

Abstract: Grit is the capacity to persevere, to have passion, and be committed to achieve goals long-term regardless of adversity or challenge. Grit provides an insight into why some nursing students succeed academically or clinically, while others do not. This quantitative cross-sectional correlational study measured levels of grit among nursing students undertaking a three-year bachelor’s degree program. All students (n = 2349) within the program were invited to complete a questionnaire which included the short grit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Duckworth 60 reports individuals with grit scores of 3.8 or higher exceed the scores of most the adult population indicating greater perseverance of effort and consistency of interest. The mean grit score for our study participants was 3.73 which is consistent with reports from others who studied DPT students 35-37,45 and health care professional students 28,61-64 and closely aligns with Duckworth's findings. Grit scores for students at Husson University were significantly greater than students at George Washington University, however, the effect size was small and likely not meaningful.…”
Section: Discussionsupporting
confidence: 91%
“…Duckworth 60 reports individuals with grit scores of 3.8 or higher exceed the scores of most the adult population indicating greater perseverance of effort and consistency of interest. The mean grit score for our study participants was 3.73 which is consistent with reports from others who studied DPT students 35-37,45 and health care professional students 28,61-64 and closely aligns with Duckworth's findings. Grit scores for students at Husson University were significantly greater than students at George Washington University, however, the effect size was small and likely not meaningful.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, students who are 'grittier' earn higher marks than those who are not ( Schimschal et al, 2021 ). A study of grit among Australian nursing students found that year level is a predictor of grit, with first-year students having lower grit levels than students in succeeding years of the program ( Terry & Peck, 2020 ). Supporting our findings, Korean nursing students demonstrated that when relevant positive psychology programs are included in the curriculum, positive thinking stimulates more optimism and produces a positive life experience throughout nursing studies, regardless of gender ( Çelik & Sarıçam, 2018 ; Han et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of nursing education resulting from the pandemic cannot be neglected, but it should not be exaggerated as well. Regarding nursing students, if there is one positive aspect of this pandemic, protective traits such as grit and positive thinking have become more prominent in them ( Terry & Peck, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study done among nursing students, 60.7% had moderate GRIT levels. 21 The variation in the proportion and mean score may be due to varied study populations, study settings, and criteria in selecting subjects.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Also, the mean score was taken by dividing the total score by the total number of questions, and classification was made as high for GRIT > 3.5, moderate for GRIT = 3–3.5, and low for GRIT < 3. 21 The study outcome measured was the mean score of GRIT, and predictors included age, sex, number of siblings, class of study, residential area, and other personal details like hours of study, extracurricular activities, time spent for the above, and parents’ details like education and annual income.…”
Section: Methodsmentioning
confidence: 99%